2022
DOI: 10.14475/jhpc.2022.25.4.150
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the End-of-Life Care of Cancer Patients Who Died in a Korean Tertiary Hospital: A Retrospective Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has caused global excess mortality [1]. In addition to quantitative changes, social distancing and hospital policies such as visitor restrictions have left seriously ill patients isolated, even dur-ing the end of life (EOL) [2], leading to qualitative changes in EOL care. This problem is not entirely specific to the CO-VID-19 pandemic, as healthcare systems have been radically overwhelmed in previous epidemics and pandemics of severe acute respiratory syndrome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A small number of studies from other countries have reported on hospice utilization during the COVID-19 outbreak, with varying results [ 4 , 5 ]. In Korea, one recent study indicated that end-of-life (EOL) care for patients with cancer worsened during the pandemic [ 6 ]; however, that study relied on indirect indicators such as distressing symptoms identified through chart audits, medical procedures performed in the dying phase, consultations for hospice care, place of death, and aggressive care in the final months. The indicators we employed exhibit greater validity, considering that the primary objective of hospice is to provide comfort to patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies from other countries have reported on hospice utilization during the COVID-19 outbreak, with varying results [ 4 , 5 ]. In Korea, one recent study indicated that end-of-life (EOL) care for patients with cancer worsened during the pandemic [ 6 ]; however, that study relied on indirect indicators such as distressing symptoms identified through chart audits, medical procedures performed in the dying phase, consultations for hospice care, place of death, and aggressive care in the final months. The indicators we employed exhibit greater validity, considering that the primary objective of hospice is to provide comfort to patients and their families.…”
Section: Discussionmentioning
confidence: 99%